Role of Ly49 Receptors on Natural Killer Cells During Influenza Virus Infection - Mahmoud, Ahmad (2012)
Natural killer (NK) cells are lymphocytes of the innate immune system that play a major role in the destruction of both tumours and virally-infected cells. The cytotoxicity of NK cells is tightly controlled by signals received through activating and inhibitory receptors. NK cells express a variety of inhibitory receptors such as Ly49 receptors. Ly49 receptors bind to class I MHC molecules that expressed on normal cells. Using Ly49-deficient (NKCKD) mice we show that Ly49-KD NK cells successfully recognize and kill influenza virus-infected cells and that NKCKD mice exhibit better survival than wild-type mice. Moreover, influenza virus infection has a propensity to upregulate cell surface expression of MHC-I on murine lung epithelial cells in vivo. Significantly, we demonstrate increased lung damage of WT-mice versus NKCKD mice after influenza virus infection as determined by histological analyses. This data indicated that absence of Ly49 inhibitory NK receptors greatly enhances survival of infected mice.